Meridional variations in stratospheric acetylene and ethane in the southern hemisphere of the saturnian atmosphere as determined from Cassini/CIRS measurements - Howett, C; Irwin, P; Teanby, N; Simon-Miller, A; Calcutt, S; Fletcher, L; de Kok, R (2007)
These are the first results from nadir studies of meridional variations in the abundance of stratospheric acetylene and ethane from Cassini/CIRS data in the southern hemisphere of Saturn. High resolution, 0.5 cm-1, CIRS data was used from three data sets taken in June-November 2004 and binned into 2° wide latitudinal strips to increase the signal-to-noise ratio. Tropospheric and stratospheric temperatures were initially retrieved to determine the temperature profile for each latitude bin. The stratospheric temperature at 2 mbar increased by 14 K from 9° to 68° S, including a steep 4 K rise between 60° and 68° S. The tropospheric temperatures showed significantly more meridional variation than the stratospheric ones, the locations of which are strongly correlated to that of the zonal jets. Stratospheric acetylene abundance decreases steadily from 30 to 68° S, by a factor of 1.8 at 2.0 mbar. Between 18° and 30° S the acetylene abundance increases at 2.0 mbar. Global values for acetylene have been calculated as (1.9 ± 0.19) × 10-7 at 2.0 mbar, (2.6 ± 0.27) × 10-7 at 1.6 mbar and (3.1 ± 0.32) × 10-7 at 1.4 mbar. Global values for ethane are also determined and found to be (1.6 ± 0.25) × 10-5 at 0.5 mbar and (1.4 ± 0.19) × 10-5 at 1.0 mbar. Ethane abundance in the stratosphere increases towards the south pole by a factor of 2.5 at 2.0 mbar. The increase in stratospheric ethane is especially pronounced polewards of 60° S at 2.0 mbar. The increase of stratospheric ethane towards the south pole supports the presence of a meridional wind system in the stratosphere of Saturn. © 2007 Elsevier Inc. All rights reserved.